Optimalisasi Pemantauan Deteksi Dini Tumbuh Kembang Anak melalui Aplikasi “PRIMAKU” - Inung Diah Kurniawati; Oyin Anjam Ainurrosidah (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
Monitoring children's growth and development is crucial. Children's growth and development needs to be done from an early age, so that children's development can grow optimally. Monitoring of children's growth and development is carried out by trained health workers and also by the child's parents. The process of monitoring children's growth and development can be done through posyandu activities and can also be done through applications. One of them is the "PRIMAKU" application which can be downloaded from Playstore. By using this application, it is hoped that parents can monitor their child's development from an early age. Therefore, there is a need for training in the introduction and use of this application. This training was carried out in Mojorayung Village, Wungu District, Kediri Regency. The targets of this training are Posyandu cadres, BKB cadres, and mothers with toddlers. The methods used in this service are preparation, implementation and evaluation. This training activity really helps cadres and mothers of toddlers in utilizing the "PRIMAKU" application. Based on the evaluation results, it was found that 95% of the training participants understood and were able to run the "PRIMAKU" application.